ANALISIS KELAYAKAN AIR DAS TALAWAAN SEBAGAI SUMBER AIR IRIGASI - Stehvani Regina Sigar; David P. Rumambi; Ruland A. Rantung (Universitas Sam Ratulangi, 2019)
ABTRACTThis research aims to determine the feasibility of the Talawaan river basin as a source ofirrigation water in the Talawaan weir based on electrical power (DHL), adsorption ratio(SAR/Sodium Adsorption Ratio), boron, pH, mercury and cyanide. This research was conductedin the Talawaan weir North Minahasa Regency, in the Baristand Laboratory (Industry Researchand Standardization Hall) and the Water Laboratory Nusantara (WLN). Sampling is purposive atfive point of sampling location with two repetitions, during drought (period I) and during rain(period II) so that samples amounted to 10 samples. The measurement results obtained from thelaboratory compared with the criteria of the quality raw irrigation water in a descriptive. Theresults showed that the six variables measured were still below the maximum level of qualitystandards so that water is categorized worthy of use as water for irrigation.Keywords: quality of irrigation water, DHL, SAR, Boron, Mercury, Cyanide